DEGREE OF STUDY OF THE CATEGORY AUTHORIZATION AT TEXT LEVEL (Scientific journal of the Fergana State University, 2024)
This article talks about the essence of the authorization category. It is noted that authorization is a term used to classify information in terms of its source. At the same time, written and oral speech is divided on the basis of “one’s own” and “alien.” Information transmitted on behalf of the first person is considered to belong to “oneself”, the information belongs to a third party, that is, “stranger”, and when it is such, its source is “In their opinion”. Scientists believe...", "According to experts", "According to rumors...", etc. this is shown by expressions. Authorization is assessed as an appeal to the owner of knowledge and opinion, the subject of illocutionary force. Authorization helps express the author's communicative intent and helps the recipient understand the author's intent. The article also analyzes the text-forming features of authorization. In particular, it is recognized as an important factor preserving the integrity of a literary text. In a scientific text, it has a systemic influence on the formation of the text and determines its compositional and semantic structure.